ANALISIS MOTIVASI DOSEN SERTA PENGARUHNYA TERHADAP PENINGKATAN KINERJA DOSEN POLITEKNIK NEGERI MALANG - Wiwaha, Sigit Setya; Sucipto, Hari; Hakim, Muhammad Fahmi (DINAMIKA DOTCOM, 2018)
The purpose of this study are : (1) To analyze the effect of the significance of Compensation for Motivation lecturer at the Polytechnic of Malang, (2) To analyze the effect of the significance of Compensation for Performance lecturer at the Polytechnic of Malang, (3) To analyze the effect of the significance of Competence on Motivation lecturer at the Polytechnic of Malang, (4) to analyze the effect of the significance of competence on the performance of a lecturer at the Polytechnic of Malang, (5) to analyze the effect of the significance of motivation on the performance of a lecturer at the Polytechnic of Malang, (6) to analyze the effect of the significance of Compensation and Competence to performance with variable between motivation at Politeknik Negeri Malang. In this study, the design used is the analysis of the design Explanantif Path (Path Analysis) to measure the relationship between variables research or to analyze how the influence of a variable to another variable. Data collection techniques in this study using a survey method, with tools enclosed questionnaire, in which respondents choose one of the answers that have been provided with alternative answers consisted of the interval is 1 - 5. The object of the study was 42 faculty of electrical engineering courses Politeknik Negeri Malang. This study found evidence that: (1) Compensation positive effect but not significant to the motivation of lecturers polytechnic poor, (2) Competence positive and significant effect on the motivation of lecturers polytechnic unfortunate, (3) Compensation positive effect but not significant to the performance professor polytechnic land poor, (4) competence positive effect but not significant to the performance professor polytechnic unfortunate, (5) Motivation positive influence and significant impact on the performance of lecturers polytechnic unfortunate, (6) There is a positive effect and significant compensation, competencies through motivation on the performance of lecturers polytechnic unfortunate.Â Keywords: Compensation, Competency, Motivation and Performance Lecturer